Biomass modified polyurethane foam as well as preparation method and application thereof in micro-nano plastic adsorption
By introducing lignin and/or tannin into the polyurethane foam, and using its chemical effect with micro-nanoplastics, the problem of difficulty in removing micro-nanoplastics in the prior art is solved, and efficient adsorption of nano-scale plastics and renewability of materials are achieved.
Patent Information
- Application Number
- CN202510005260.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-03
- Publication Date
- 2025-04-01
AI Technical Summary
The prior art is difficult to effectively remove micro-nanoplastics from water, especially the removal rate of nano-scale plastics with smaller sizes is low.
Adsorption of micro-nanoplastics is achieved by introducing lignin and/or tannic acid as functional monomers into the polyurethane foam, and the electrostatic action, hydrogen bonding or π-π conjugation between its porous structure and characteristic functional groups and the micro-nanoplastics.
The prepared biomass modified polyurethane foam not only has a strong adsorption effect on nanoplastics of 70~80nm, but also has strong regeneration ability, which can effectively solve the pollution problem of nanoplastics in water.
Smart Images

Figure CN119735785A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of polyurethane adsorption materials, and specifically relates to a biomass modified polyurethane foam and a preparation method thereof and application thereof in micro-nano plastic adsorption. Background Art
[0002] Plastic is a material with synthetic or natural polymer compounds as its main component. Due to its advantages such as inertness, high strength, durability, light weight and affordability, it has become one of the most in-demand synthetic materials today, and is growing rapidly at a rate of 320 million tons per year, and is expected to double in the next 20 years. However, while plastic provides convenience for human life and production, it also pollutes the marine environment due to improper handling during use or post-processing.
[0003] Moreover, due to the high molecular weight, stable carbon chain structure, complex three-dimensional structure and hydrophobicity of plastics (such as polyethylene (PE), polypropylene (PP), polystyrene (PS), polyvinyl chloride (PVC), etc.), even after long-term mechanical wear, biodegradation, hydrolysis, heat and light irradiation and other weathering conditions, they can only be degraded into microplastics (MPs, 100 nm < 5 mm) or nanoplastics (NPs, < 100 nm). These MPs and NPs not only harm aquatic organisms and marine ecosystems in the long term, but also enter the human body through the food chain. Through their large specific surface area and volume ratio, they continuously enrich metals and harmful substances in the human body, making it impossible for them to be discharged normally, and ultimately leading to metabolic disorders and cytotoxicity in the human body.
[0004] Therefore, it is of vital importance to solve the pollution problem of micro-nano plastics (MNPs) in water. At present, the methods to reduce the pollution of micro-nano plastics in water mainly include flotation filtration, coagulation, flocculation, precipitation, coagulation-flocculation-precipitation, membrane separation, microbial degradation, photocatalysis and adsorption. However, flotation filtration, coagulation, flocculation and precipitation mainly change the aggregation state of MNPs by magnetism or gravity, and then separate MNPs from liquid. This method has high requirements on the composition and size of MNPs, and usually can only remove larger MNPs, and the removal rate of smaller MNPs (<10μm) is low. Membrane separation mainly adjusts the size of the filter membrane to block microplastics, thereby achieving solid-liquid separation. Although this method shows a high removal rate for smaller MNPs (<5μm), it takes a long time and the membrane is easily blocked and contaminated, resulting in high operating costs. The microbial degradation method mainly uses microbial enzymes to decompose MNPs into smaller fragments, and then completely degrades them through mineralization. However, this method is limited in scope due to the long treatment time (7–40 days) and the scarcity of available biological enzymes. The photocatalytic method mainly decomposes MNPs into carbon dioxide and water-soluble hydrocarbons through the catalytic effect of light. It is an environmentally friendly and low-cost method for microplastic degradation. However, most MNPs can only be partially degraded under pure ultraviolet light, so the degradation efficiency is low. The adsorption method mainly uses some porous structure materials as matrix materials to provide a driving force for the diffusion of MNPs in the material, and then introduces some characteristic functional groups into the material to modify the material, and uses the electrostatic interaction, hydrogen bonding, van der Waals force or π-π conjugation between these functional groups and MNPs to achieve the purpose of adsorbing MNPs. Among them, the adsorption method is widely used in the microplastic treatment process because of its adjustable material structure, high adsorption capacity and reusability. The materials currently used to adsorb microplastics in water mainly include MOFs, carbon materials, polymer adsorption materials, etc. Among the above adsorption materials, MOFs and carbon materials are difficult to use in large quantities due to their complex preparation process, high production cost, and low yield. In contrast, polymer materials have significant advantages in microplastic treatment due to their adjustable structure, simple preparation process, and mass production. However, although existing polymer materials have played an important role in the adsorption of microplastics, the MNPs they adsorb are mainly micron-sized plastics, and there is little research on the adsorption of smaller nanoplastics. Summary of the invention
[0005] In view of the difficulty in handling micro-nano plastics in the prior art, the present invention provides a biomass-modified polyurethane foam, a preparation method thereof, and an application in the adsorption of micro-nano plastics. Lignin and / or tannic acid are introduced as functional monomers into polymer porous materials, which can not only solve the pollution problem of micro-nano plastics in the environment, but also provide an opportunity to expand the application field of biomass materials.
[0006] The present invention is achieved through the following technical solutions: A method for preparing biomass modified polyurethane foam comprises dissolving lignin and / or tannic acid, mixing with polyurethane foam prepolymer, stirring and foaming, and washing and drying after forming and maturing to obtain biomass modified polyurethane foam.
[0007] Furthermore, the polyurethane foam prepolymer comprises polyether or polyester polyol, isocyanate, a catalyst and a foaming agent.
[0008] Furthermore, the average molecular weight of the polyether or polyester polyol is 2000-8000 g / mol; the isocyanate is one or more of toluene diisocyanate, polymethylene polyphenyl isocyanate and diphenylmethane diisocyanate; the catalyst is one or more of triethylenediamine (TEDA), stannous octoate and tin isooctanoate (TECH); and the blowing agent is water or ethanol. Furthermore, the mass ratio of the polyether or polyester polyol to the isocyanate is 2:1~1:2; the added amount of the catalyst is 0.05~0.5% of the mass of the polyether or polyester polyol and the isocyanate; and the added amount of the foaming agent is 0.5~2% of the mass of the polyether or polyester polyol and the isocyanate.
[0009] Furthermore, lignin and tannic acid are dissolved, mixed with polyurethane foam prepolymer, stirred and foamed, and after being formed and matured, washed and dried to obtain biomass modified polyurethane foam.
[0010] Further, the amount of tannic acid or lignin or a mixture thereof is 0.7-3% of the total amount of polyurethane foam. Furthermore, the mass ratio of lignin to tannic acid is 1:3-3:1; preferably 1:1-1:2.
[0011] Furthermore, the dissolving solvent is N,N-dimethylformamide, and the mass ratio of lignin and / or tannic acid to N,N-dimethylformamide is 1:15~1:3.3; the stirring and foaming rate is 100~300r / min; the washing solvent is water; and the drying is freeze-drying.
[0012] In the present invention, the biomass-modified polyurethane foam is prepared by the above-mentioned preparation method.
[0013] In the present invention, the biomass modified polyurethane foam is used in the adsorption of micro-nano plastics.
[0014] Furthermore, the micro-nano plastic is nano plastic.
[0015] In the present invention, lignin and tannic acid are biomass materials abundant in nature, and their molecular structures contain a large number of hydroxyl groups and benzene rings. They are introduced into the polymer porous material as functional monomers, and the porous structure of the polymer material is utilized to expose the characteristic functional groups of lignin, tannic acid and the material itself, thereby improving the transmission rate of MNPs in the material, and adsorbing MNPs through the electrostatic interaction, hydrogen bonding or π-π conjugation between these characteristic functional groups and MNPs, thereby solving the problem of removing MNPs in water.
[0016] Beneficial Effects The biomass-modified polyurethane foam prepared by the present invention not only has a strong adsorption effect on nanoplastics with a diameter of about 70 to 80 nm, but also has a strong regeneration ability after repeated use through a certain desorption method. It can not only solve the pollution problem of nanoplastics in the environment, but also provide an opportunity for expanding the application field of biomass materials. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] Figure 1 This is a graph showing the renewability test results of different biomass-modified polyurethane foams. DETAILED DESCRIPTION
[0018] The following is a further description of a biomass-modified polyurethane foam for removing micro-nano plastics in water in conjunction with specific examples. The specific examples are for further illustrating the present invention in detail, but do not limit the scope of protection of the present invention. Unless otherwise specified, the reagents, equipment and methods used in the present invention are conventional commercially available reagents, equipment and conventionally used methods in the art.
[0019] Example 1 0.105g lignin was dissolved in 1.5g N,N-dimethylformamide and completely dissolved by ultrasonication; then it was mixed with 10g polyether polyol (Mn=2000g / mol), 5g diphenylmethane diisocyanate, 0.0075g triethylenediamine and 0.075g water, and stirred and foamed at 25°C and 100r / min for 20s. After forming and maturing, it was immersed in deionized water and washed repeatedly for 3 times under ultrasonic oscillation, and then placed in a freeze dryer for freeze drying for 24h to obtain biomass (lignin) modified polyurethane foam.
[0020] Example 2 0.105g of tannic acid was dissolved in 1.5g of N,N-dimethylformamide and dissolved completely by ultrasonication. Then it was mixed with 10g of polyether polyol (Mn=2000g / mol), 5g of diphenylmethane diisocyanate, 0.0075g of triethylenediamine and 0.075g of water, stirred and foamed at 25℃ and 100r / min for 20s, and after forming and maturing, it was immersed in deionized water and repeatedly washed 3 times under ultrasonic oscillation, and then placed in a freeze dryer for 24h to obtain biomass (tannic acid) modified polyurethane foam.
[0021] Example 3 0.45g lignin was dissolved in 1.5g N,N-dimethylformamide and completely dissolved by ultrasonication; then it was mixed with 10g polyether polyol (Mn=2000g / mol), 5g diphenylmethane diisocyanate, 0.0075g triethylenediamine and 0.075g water, and stirred and foamed at 25°C and 100r / min for 20s. After forming and maturing, it was immersed in deionized water and washed repeatedly for 3 times under ultrasonic oscillation, and then placed in a freeze dryer for freeze drying for 24h to obtain biomass (lignin) modified polyurethane foam.
[0022] Example 4 0.45g of tannic acid was dissolved in 1.5g of N,N-dimethylformamide and dissolved completely by ultrasonication. Then it was mixed with 10g of polyether polyol (Mn=2000g / mol), 5g of diphenylmethane diisocyanate, 0.0075g of triethylenediamine and 0.075g of water, stirred and foamed at 25℃ and 100r / min for 20s, and after forming and maturing, it was immersed in deionized water and repeatedly washed 3 times under ultrasonic oscillation, and then placed in a freeze dryer for 24h to obtain biomass (tannic acid) modified polyurethane foam.
[0023] Example 5 0.05g tannic acid and 0.05g lignin were dissolved in 1.5g N,N-dimethylformamide and completely dissolved by ultrasonication; then, they were mixed with 10g polyether polyol (Mn=2000g / mol), 5g diphenylmethane diisocyanate, 0.0075g stannous octoate and 0.075g water, and stirred and foamed for 20s at a stirring rate of 100r / min at 25°C. After forming and maturing, they were immersed in deionized water and washed repeatedly for 3 times under ultrasonic oscillation, and then placed in a freeze dryer for freeze drying for 24h to obtain biomass (lignin and tannic acid) modified polyurethane foam.
[0024] Example 6 0.025g tannic acid and 0.075g lignin were dissolved in 1.5g N,N-dimethylformamide and completely dissolved by ultrasonication; then, they were mixed with 10g polyether polyol (Mn=2000g / mol), 5g diphenylmethane diisocyanate, 0.0075g stannous octoate and 0.075g water, and stirred and foamed at 25°C and 100r / min for 20s. After forming and maturing, they were immersed in deionized water and washed repeatedly for 3 times under ultrasonic oscillation, and then placed in a freeze dryer for freeze drying for 24h to obtain biomass (lignin and tannic acid) modified polyurethane foam.
[0025] Example 7 0.075g tannic acid and 0.025g lignin were dissolved in 1.5g N,N-dimethylformamide and completely dissolved by ultrasonication; then, they were mixed with 10g polyether polyol (Mn=2000g / mol), 5g diphenylmethane diisocyanate, 0.0075g tin isooctanoate and 0.075g water, and stirred and foamed at 25°C and 100r / min for 20s. After forming and maturing, they were immersed in deionized water and washed repeatedly for 3 times under ultrasonic oscillation, and then placed in a freeze dryer for freeze drying for 24h to obtain biomass (lignin and tannic acid) modified polyurethane foam.
[0026] Example 8 0.05g tannic acid and 0.05g lignin were dissolved in 1.5g N,N-dimethylformamide and completely dissolved by ultrasonication; then, they were mixed with 10g polyether polyol (Mn=8000g / mol), 5g diphenylmethane diisocyanate, 0.075g tin isooctanoate and 0.45g water, and foamed at 25°C and 100r / min for 20s. After forming and maturing, the mixture was immersed in deionized water and washed repeatedly for 3 times under ultrasonic oscillation, and then freeze-dried in a freeze dryer for 24h to obtain biomass (lignin and tannic acid) modified polyurethane foam.
[0027] Example 9 0.225g tannic acid and 0.225g lignin were dissolved in 1.5g N,N-dimethylformamide and completely dissolved by ultrasonication; then, they were mixed with 10g polyester polyol (Mn=5000g / mol), 5g diphenylmethane diisocyanate, 0.075g tin isooctanoate and 0.45g water, and foamed at 25°C and 100r / min for 20s. After forming and maturing, they were immersed in deionized water and washed repeatedly for 3 times under ultrasonic oscillation, and then freeze-dried in a freeze dryer for 24h to obtain biomass (lignin and tannic acid) modified polyurethane foam.
[0028] Example 10 0.225g tannic acid and 0.225g lignin were dissolved in 1.5g N,N-dimethylformamide and completely dissolved by ultrasonication; then, they were mixed with 10g polyether polyol (Mn=8000g / mol), 5g polymethylene polyphenyl isocyanate, 0.075g triethylenediamine and 0.45g ethanol, stirred and foamed at 25°C and 100r / min for 20s, and after forming and maturing, they were immersed in deionized water and washed repeatedly for 3 times under ultrasonic oscillation, and then placed in a freeze dryer for freeze drying for 24h to obtain biomass (lignin and tannic acid) modified polyurethane foam.
[0029] Embodiment 11 0.15g tannic acid and 0.3g lignin were dissolved in 1.5g N,N-dimethylformamide and completely dissolved by ultrasonication; then, they were mixed with 10g polyether polyol (Mn=8000g / mol), 5g toluene diisocyanate, 0.05g triethylenediamine and 0.3g water, stirred and foamed at 25°C and 100r / min for 20s. After forming and maturing, they were immersed in deionized water and washed repeatedly for 3 times under ultrasonic oscillation, and then placed in a freeze dryer for freeze drying for 24h to obtain biomass (lignin and tannic acid) modified polyurethane foam.
[0030] Example 12 0.3g tannic acid and 0.15g lignin were dissolved in 1.5g N,N-dimethylformamide and completely dissolved by ultrasonication; then, they were mixed with 5g polyether polyol (Mn=8000g / mol), 10g diphenylmethane diisocyanate, 0.05g triethylenediamine and 0.3g ethanol, stirred and foamed at 25°C and 100r / min for 20s. After forming and maturing, they were immersed in deionized water and washed repeatedly for 3 times under ultrasonic oscillation, and then placed in a freeze dryer for freeze drying for 24h to obtain biomass (lignin and tannic acid) modified polyurethane foam.
[0031] Embodiment 13 0.15g tannic acid and 0.15g lignin were dissolved in 1.5g N,N-dimethylformamide and completely dissolved by ultrasonication; then, they were mixed with 5g polyester polyol (Mn=8000g / mol), 10g diphenylmethane diisocyanate, 0.05g triethylenediamine and 0.3g ethanol, stirred and foamed at 25°C and 100r / min for 20s. After forming and maturing, they were immersed in deionized water and washed repeatedly for 3 times under ultrasonic oscillation, and then placed in a freeze dryer for freeze drying for 24h to obtain biomass (lignin and tannic acid) modified polyurethane foam.
[0032] Embodiment 14 0.1g tannic acid and 0.2g lignin were dissolved in 1.5g N,N-dimethylformamide and completely dissolved by ultrasonication; then, they were mixed with 5g polyether polyol (Mn=8000g / mol), 10g diphenylmethane diisocyanate, 0.05g tin isooctanoate and 0.3g ethanol, stirred and foamed at 25°C and 300r / min for 20s. After forming and maturing, they were immersed in deionized water and washed repeatedly for 3 times under ultrasonic oscillation, and then placed in a freeze dryer for freeze drying for 24h to obtain biomass (lignin and tannic acid) modified polyurethane foam.
[0033] Comparative Example 1 10g of polyether polyol (Mn=2000g / mol), 5g of diphenylmethane diisocyanate, 0.0075g of triethylenediamine and 0.075g of water were mixed, stirred and foamed at 25°C and a stirring rate of 100r / min for 20s. After molding and maturation, the mixture was immersed in deionized water and washed repeatedly for 3 times under ultrasonic oscillation, and then placed in a freeze dryer for freeze drying for 24h to obtain polyurethane foam.
[0034] Comparative Example 2 10g of polyether polyol (Mn=8000g / mol), 5g of toluene diisocyanate, 0.05g of triethylenediamine and 0.3g of water were mixed, stirred and foamed at 25°C and 100r / min for 20s. After forming and maturing, the mixture was immersed in deionized water and washed repeatedly for 3 times under ultrasonic oscillation, and then placed in a freeze dryer for freeze drying for 24h to obtain polyurethane foam.
[0035] Comparative Example 3 5g of polyester polyol (Mn=8000g / mol), 10g of diphenylmethane diisocyanate, 0.05g of triethylenediamine and 0.3g of ethanol were mixed, stirred and foamed at 25°C and a stirring rate of 100r / min for 20s. After forming and maturing, the mixture was immersed in deionized water and washed repeatedly for 3 times under ultrasonic oscillation, and then placed in a freeze dryer for freeze drying for 24h to obtain polyurethane foam.
[0036] 0.1 g of each of the biomass-modified polyurethane foam prepared in the above embodiment and the polyurethane foam prepared in the comparative example was placed in 100 mL of 300 mg / L nanoplastic dispersion (polystyrene microspheres: size 70-80 nm), and then subjected to oscillation adsorption reaction at 25° C. for 2 h. By measuring the change in the concentration of nanoplastics before and after the reaction, the adsorption amount of nanoplastics by different polyurethane foams was calculated. The calculation formula is as follows: Q m = (C0-C) × V / m0 Where Q mis the adsorption amount of nanoplastics by different polyurethane foams (mg / g); C0 is the initial concentration of nanoplastics (mg / L); C is the concentration of nanoplastics after adsorption (mg / L); V is the volume of nanoplastics (mL); m is the mass of nanoplastics (g).
[0037] Adsorption performance test (1) The adsorption amount of nanoplastics by the biomass-modified polyurethane foam prepared in the example and the polyurethane foam prepared in the comparative example is shown in Table 1 below. As can be seen from Table 1, when lignin or tannic acid is added to the polyurethane foam (especially a mixture of lignin and tannic acid), the adsorption amount of nanoplastics by the biomass-modified polyurethane foam is significantly improved.
[0038] Table 1 Adsorption of nanoplastics by biomass-modified polyurethane foam and polyurethane foam prepared in comparative example .
[0039] (2) In order to prove the removal effect of the polyurethane foam prepared in the above embodiment on low-concentration nanoplastics, the present invention uses 10 mg / L nanoplastics as the research object to prove the removal rate of polyurethane foam on nanoplastics. And calculate the removal rate. The calculation method of the removal rate is as follows: υ = V(C0-C) / VC0×100% in: υ-removal rate of nanoplastics by polyurethane foam, %; V-volume of polyurethane foam, mL; C0-concentration of polyurethane foam before adsorption, mg / L; C-concentration of polyurethane foam after adsorption, mg / L.
[0040] The removal rates of 10 mg / L nanoplastics by the biomass-modified polyurethane foam prepared in the example and the polyurethane foam prepared in the comparative example are shown in Table 2 below. As can be seen from Table 2, when lignin or tannic acid is added to the polyurethane foam (especially a mixture of lignin and tannic acid), the removal rate of nanoplastics by the biomass-modified polyurethane foam is significantly improved.
[0041] Table 2 Removal rate of nanoplastics by biomass-modified polyurethane foam and polyurethane foam prepared in comparative example.
[0042] .
[0043] (3) In order to prove the reproducibility of biomass-modified polyurethane foam, the present invention placed the biomass-modified polyurethane foam after adsorbing nanoplastics in distilled water and 95% ethanol for ultrasonic oscillation desorption for 20 minutes, and then reused it for the adsorption experiment of nanoplastics. The results showed that after repeated 6 times, the polyurethane foam still had a high adsorption capacity (>80%) for nanoplastics. The experimental results are as follows: Figure 1 As shown by Figure 1 It can be seen that the biomass-modified polyurethane foam prepared by the present invention not only has a high nanoplastic adsorption capacity, but also has strong renewability.
Claims
1. A method for preparing biomass-modified polyurethane foam, characterized in that: The lignin and / or tannic acid are dissolved, mixed with the polyurethane foam prepolymer, stirred and foamed, and after being formed and matured, washed and dried to obtain the biomass modified polyurethane foam.
2. The method for preparing biomass-modified polyurethane foam according to claim 1, characterized in that: The polyurethane foam prepolymer comprises polyether or polyester polyol, isocyanate, a catalyst and a foaming agent.
3. The method for preparing biomass-modified polyurethane foam according to claim 2, characterized in that: The average molecular weight of the polyether or polyester polyol is 2000-8000 g / mol; the isocyanate is one or more of toluene diisocyanate, polymethylene polyphenyl isocyanate and diphenylmethane diisocyanate; the catalyst is one or more of triethylenediamine, stannous octoate and tin isooctanoate; and the blowing agent is water or ethanol.
4. The method for preparing biomass-modified polyurethane foam according to claim 2, characterized in that: The mass ratio of the polyether or polyester polyol to the isocyanate is 2:1-1:2; the added amount of the catalyst is 0.05-0.5% of the mass of the polyether or polyester polyol and the isocyanate; and the added amount of the foaming agent is 0.5-2% of the mass of the polyether or polyester polyol and the isocyanate.
5. The method for preparing biomass-modified polyurethane foam according to claim 1, characterized in that: The lignin and tannic acid are dissolved, mixed with the polyurethane foam prepolymer, stirred and foamed, and after being formed and matured, washed and dried to obtain the biomass modified polyurethane foam.
6. The method for preparing biomass-modified polyurethane foam according to claim 5, characterized in that: The mass ratio of lignin to tannic acid is 1:3-3:1, preferably 1:1-1:
2.
7. The method for preparing biomass-modified polyurethane foam according to claim 1, characterized in that: The dissolving solvent is N, N-dimethylformamide, and the mass ratio of lignin and / or tannic acid to N, N-dimethylformamide is 1:15-1:3; the stirring and foaming rate is 100-300 r / min; the washing solvent is water; and the drying is freeze drying.
8. A biomass-modified polyurethane foam prepared by the preparation method according to any one of claims 1 to 7.
9. Use of the biomass-modified polyurethane foam according to claim 8 in the adsorption of micro-nano plastics.
10. The use according to claim 9, characterized in that: The micro-nano plastic is nano plastic.
Citation Information
Patent Citations
Preparation method and application of plant polyphenol modified polyurethane foam
CN113234204A
Microplastic degradation method
CN118751665A
Cited By
Cellulose fiber-based sandwich structure filter material for removing micro-plastics and preparation method of cellulose fiber-based sandwich structure filter material
CN121648646A
Preparation method and application of magnetic hydroxyapatite material
CN122006654A